Malignant Hypertension in the Al-Thawarah Hospital-Sana’a - Al-Zendani, Aziz S.; Al-Motarreb, Ahmed L.; Al-Qudari , Elham (Thamar University Journal of Natural & Applied Sciences, 2023)
Background: Malignant hypertension (MHTN) is characterized by very high blood pressure (BP), and organ damage. It is a complication of uncontrolled hypertension. Malignant hypertension requires immediate treatment and admission to the hospital to manage and control the high elevation of the blood pressure. Systemic hypertension is increasing in our society in recent years due to the changes in the lifestyle of the Yemenis and chewing Khat in large scale in most governments than before. Hypertension is a silent disease in which the majority of patients do not have symptoms. Lack of early detection, proper management of hypertension, routine medical check up and awareness of the society, lead to the malignant hypertension and its end organ damage.Aim of the study: To study the clinical presentation and complications of the malignant hypertension in patients admitted to the cardiac centre at Al thawrah hospital (TMGH), Sanaa in one year time (May 2009-May 2010)Method of the study: Descriptive Study including all patients admitted to the cardiac centre at TMGH, Sanaa with a diagnosis of MHTN between May 2009-May 2010.Results: 16 cases were reported, with a mean age of 54.7± 7.8 years. 65.3% of them were male. A 62.5% (10 patients) discovered to have HTN on admission, and 37.5 % (6 patients) were presented with history of hypertension, only 2 of them (12.5%) were on antihypertension medication but with improper doses and 25% (4 patients) refused to take medications. The measurement of the systolic BP on admission showed 81.2% (13 cases) had systolic BP between 180-200 mmHg ,12.5% (2cases) were between 210-220 mmHg and 6.25%(1case) the reading was 240mmHg , 50% (8 patients) had a diastolic BP of 130 mmHg, 25% (4 cases) had >130mmHg and 18.7% (3 cases) was